GUP1 and its close homologue GUP2, encoding multi-membrane-spanning proteins involved in active glycerol uptake in Saccharomyces cerevisiae - Holst, Bjørn (2000)
Many yeast species can utilise glycerol, both as sole carbon source and as an osmolyte. In Saccharomyces cerevisiae, physiological studies have previously shown the presence of an active uptake system driven by electrogenic proton symport. We have used transposon mutagenesis to isolate mutants affected in the transport of glycerol into the cell. Here we present the identification of YGL084c, encoding a multi-membrane-spanning protein, as being essential for proton symport of glycerol into Saccharomyces cerevisiae. The gene is named GUP1 (Glycerol UPtake) and is important for growth on glycerol as carbon and energy source, as well as for osmotic protection by added glycerol, of a strain deficient in glycerol production. Another ORF, YPL189w, presenting a high degree of homology to YGL084c, similarly appears to be involved in active glycerol uptake in salt-containing glucose-based media in strains deficient in glycerol production. Analogously, this gene is named GUP2. To our knowledge, this is the first report on a gene product involved in active transport of glycerol in yeasts. Mutations with the same phenotypes occurred in two other open reading frames of previously unknown function, YDL074c and YPL180w.